Pertumbuhan dan Hasil Bawang Merah Terhadap Frekuensi Penyiraman dan Pupuk Boron pada Media Pasir - Maghfiroh, Putri S; .Historiawati, Historiawati; Jannah, Eka N (JURNAL BUDIDAYA PERTANIAN, 2025)
Cultivation of shallots (Allium ascalonicum L.) on suboptimal land such as sandy land is one of the efforts to increase shallot production. The nature of sandy land which has high porosity with low water binding capacity and minimal nutrients requires sufficient water supply through regulating the frequency of watering and providing boron fertilizer to increase the availability of micronutrients. This study aimed to analyze the frequency of watering and the right dose of boron fertilizer to obtain the highest growth and yield of shallots on sandy media. The study was conducted from April to July 2024 in Banjarnegoro, Mertoyudan District, Magelang Regency. The research method used a completely randomized block design consisting of two factors and three blocks as replications. The first factor was the frequency of watering with 3 levels, namely 2 times a day, 1 time a day in the morning and 1 time a day in the afternoon. The second factor was the dose of boron fertilizer with 4 levels, namely 0 g/polybag, 0.009 g/polybag, 0.0135 g/polybag, and 0.018 g/polybag. Data were analyzed using analysis of variance and further tests using 5% and 1% BNT tests. The results showed that the frequency of watering twice a day had a significant effect on the number of leaves 45 days after planting (DAF) but had no significant effect on other variabels. The dose of boron fertilizer of 0.0135 g/polybag did not significantly increase the growth and yield of shallots and there was no interaction between the two treatments.